Uma mulher : a feminilidade a partir da literatura de Clarice Lispector - Paiva, Marcela Ribeiro Pacheco (2019)
This work aims to explore the literature of Clarice Lispector regarding femininity. The objective is to examine the feminine dynamics through Clarice’s writing, in order to elaborate a reflection on the theme. It references to the Psychoanalytic Theory, with emphasis on the Lacanian approach. According to this perspective, femininity is a particular construction that conjectures inventiveness, whereas there’s a lack of representation of the female sex signifier. Hence, the partial submission to the phallic law and, consequently, the access to an Other jouissance, properly feminine, on which nothing can be said. Hence Femininity is referred to as unnameable. Therefore, the literature of Clarice Lispector implies a possibility of approximation because, by means of devices, it reveals what surpasses language. Thus, the study intends to analyze tales that allow us to discern the feminine otherness, namely: "The disasters of Sofia"; "The imitation of the rose"; "Love".